Pengembangan Potensi Peserta Didik oleh Guru Pendidikan Agama Kristen Pada Pembelajaran Pendidikan Agama Kristen di SMA Negeri 1 Siempat Nempu Hulu - Tiurmaida Nadeak (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The purpose of this study explores Christian religious education learning that develops students' potential at SMA Negeri 1 Siempat Nempu Hulu, Dairi Regency. Theories related to the contribution of Christian Religious Education teachers in developing students' character and potential are important references for analyzing the steps of activities carried out in learning. This study uses a qualitative approach with a descriptive analysis method, which involves data collection through interviews, observations, and document studies. The results of the study indicate that Christian religious education does not only focus on cognitive aspects, but also on developing students' moral and spiritual values. Through learning that is integrated with Christian values, students are taught to apply Christian values ​​in good character and independence. Thus, students are equipped with various skills from their potential so that they have an impact on their lives and the surrounding environment. The conclusion in this study emphasizes that teachers in teaching Christian education are useful in shaping character and developing students' potential, as well as providing recommendations for improving teaching methods to be more effective in achieving educational goals.